Global forest carbon uptake due to nitrogen and phosphorus deposition from 1850 to 2100. (26th June 2017) - Wang, Rong; Goll, Daniel; Balkanski, Yves; Hauglustaine, Didier; Boucher, Olivier; Ciais, Philippe; Janssens, Ivan; Penuelas, Josep; Guenet, Bertrand; Sardans, Jordi; Bopp, Laurent; Vuichard, Nicolas; et al.
Abstract: Spatial patterns and temporal trends of nitrogen (N) and phosphorus (P) deposition are important for quantifying their impact on forest carbon (C) uptake. In a first step, we modeled historical and future change in the global distributions of the atmospheric deposition of N and P from the dry and wet deposition of aerosols and gases containing N and P. Future projections were compared between two scenarios with contrasting aerosol emissions. Modeled fields of N and P deposition and P concentration were evaluated using globally distributed in situ measurements. N deposition peaked around 1990 in European forests and around 2010 in East Asian forests, and both increased sevenfold relative to 1850. P deposition peaked around 2010 in South Asian forests and increased 3.5‐fold relative to 1850. In a second step, we estimated the change in C storage in forests due to the fertilization by deposited N and P (∆Cν dep ), based on the retention of deposited nutrients, their allocation within plants, and C:N and C:P stoichiometry. ∆Cν dep for 1997–2013 was estimated to be 0.27 ± 0.13 Pg C year −1 from N and 0.054 ± 0.10 Pg C year −1 from P, contributing 9% and 2% of the terrestrial C sink, respectively. Sensitivity tests show that uncertainty of ∆Cν dep was larger from P than from N, mainly due to uncertainty in the fraction of deposited P that is fixed by soil. ∆CP dep was exceeded by ∆CN dep over 1960–2007 in a large area of East Asian and West European forests due to a faster growth in N deposition than P. Our results suggest a significant contribution of anthropogenic P deposition to C storage, and additional sources of N are needed to support C storage by P in some Asian tropical forests where the deposition rate increased even faster for P than for N. Abstract : We estimate the historical and future change in global distributions of the atmospheric deposition of N and P. We apply a stoichiometric mass‐balance approach to estimate the change in C storage in forests due to the fertilization by deposited N and P. We find that the effect of P is exceeded by N in East Asian and West European forests due to a faster growth in N deposition than P, and that there is a significant contribution of anthropogenic P deposition to C storage in some Asian tropical forests where the deposition increased even faster for P than for N.